Desain Media Bahan Ajar Berbasis Cooperative Learning pada Pembelajaran Bagian Tumbuh-Tumbuhan di Sekolah Dasar - Ayuningtyas, Zidhny Ilma; Wuryastuti, Sri; Suratno, Tatang (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Education is active, which in the world of education requires adaption to the movement of the times. So far, teachers sometimes use the old method, namely lectures in teaching. Meanwhile, the current millennial generation needs more attractive learning and something more concrete to stimulate the learning of students who have learning obstacles. This announcement is based on the researcher examining a teaching material for learning the plant part of the science subject for fourth grade of elementary school which is still not well prepared which has an impact on the occurrence of learning obstacles in students. From this case, this study aims to design cooperative learning-based teaching materials to reduce students' learning difficulties. The method used is Didactical Design Research (DDR) using 3 hierarchies, namely: 1.) prospective analysis, 2) meta-pedadidactic analysis, and 3) retrospective analysis. The results of this study developed a didactic design in the form of modules and game media to overcome student learning obstacles. After that, a final learning obstacle is tested to prove the effectiveness of the didactic design that the researcher made. 6 types of learning obstacles were found in the final test, which means that there was a decrease in the percentage of learning obstacles. The researcher compared the percentage of students who experienced learning obstacles in the initial and final test questions. In the initial test, there were 9 types of learning obstacles, and 6 types of learning obstacles in the final test. In this study, the results showed a significant decrease in students' learning obstacles. This interpretation of cooperative learning-based teaching material media design is effectively used as an alternative teaching material in conveying the learning of the plant part.